Primer uporabe matematičnih modelov - Stopar, Nik (Matematika v šoli, 2023)
This article provides an example of a secondary school modeling exercise that can be adapted for use in the final years of primary school. It was created and presented as part of the NA-MA POTi project.
Keywords: matematična pismenost; matematika; modeliranje; projekt NA-MA POTI